Is jumbo biopsy forceps comparable to cold snare for diminutive colorectal polyps? – a meta-analysis - Srinivasan, Sachin; Siersema, Peter D.; Desai, Madhav (Endoscopy International Open, 2021)
Background and study aims Diminutive colorectal polyps are increasingly being detected and it is not clear whether jumbo biopsy forceps (JBF) has comparable efficacy to that of cold snare polypectomy (CSP) for management of these lesions. Methods An electronic literature search was performed for studies comparing resection rates of JBF and CSP for diminutive polyps (≤ 5 mm). The primary outcome was incomplete resection rate (IRR). Secondary outcomes included failure of tissue retrieval and complication rates (post-polypectomy bleeding, perforation etc.). Leave-one-out analysis was performed to examine the disproportionate role of any of the studies. Meta-analysis outcomes and heterogeneity (I2) were computed using Comprehensive meta-analysis software.Results A total of 4 studies (3 randomized controlled trials and 1 retrospective study) with 407 patients and 569 total polyps (mean size of 3.62 mm) was included for analysis. IRR of JBF was slightly higher than that of CSP (10.2 % vs 7.2 %) but this was not statistically significantly different (Pooled OR 1.76; 95 % CI 0.94–3.28; I2 = 0). Leave-one-out analysis showed no significant difference in the pooled OR comparison either. Two of the 4 studies reported 0 % failure of tissue retrieval for JBF and 1 % and 4.3 % for CSP. There were no complications for either group from the 2 studies that reported this outcome. The quality of the included studies was moderate to high. Conclusions This systematic review with only limited data shows that JBF and CSP are not statistically different in completely removing diminutive polyps, although careful endoscopic assessment is needed to ensure complete removal of all polyp tissue.